ANALYSIS OF THE EFFECTIVITY OF COUPLING BEAM ON HIGH RISE-BUILDING STRUCTURE USING OUTRIGGER AND BELTTRUSS - KASLAN , DAVY
The design of high-rise building has issues in excessive lateral deformation and serviceability. The common system that is used such as coupled shearwall is no longer capable of overcome these problems for high-rise structure. In order to overcome these problem, outrigger and belttruss system is used. Commonly in coupled shearwall system, coupling beam is the main dissipator element. This research is addressed to get information of plastification hierarchy when outrigger and belttruss is added to the coupled shearwall system, and the effective L/H ratio of coupling beam. Based on nonlinear analysis which is consist of pushover analysis and time history analysis, the performance of model that is use the L/H ratio of 4 and SMF beam reinforcement is worse than model with L/H ratio of 2 and 3. This is caused by the excessive rotation of coupling beam up to 0.65 CP. Meanwhile, for model with L/H ratio of 2 and 3 with diagonal reinforcement and L/H=3 with SMF beam reinforcement have similar performance and behavior but better than model with ratio L/H=4. Besides, plastification hierarchy, for L/H=2 and 3, shift to main beam, base shearwall, shearwall at outrigger location, and mega column. So, the most effective L/H ratio of coupling beam for outrigger and belttruss system based on this research is 3 and with the use of SMF beam reinforcement (without diagonal reinforcement).